Application of herbs and active ingredients ameliorate non-alcoholic fatty liver disease under the guidance of traditional Chinese medicine - Zhou, Zhijia; Zhang, Jinghao; You, Liping; Wang, Tao; Wang, Kaixia; Wang, Lingtai; Kong, Xiaoni; Gao, Yueqiu; Sun, Xuehua (Frontiers in Endocrinology, 2022)
Non-alcoholic fatty liver disease (NAFLD) is a global health problem and its prevalence has been on the rise in recent years. Traditional Chinese Medicine (TCM) contains a wealth of therapeutic resources and has been in use for thousands of years with regard to the prevention of liver disease and has been shown to be effective in the treatment of NAFLD in China. but the molecular mechanisms behind it have not been elucidated. In this article, we have updated and summarized the research and evidence with regard to herbs and their active ingredients for the treatment in vivo and vitro models of NAFLD or NASH, by searching PubMed, Web of Science and SciFinder databases. In particular, we have found that most of the herbs and active ingredients reported so far have the effect of clearing heat and dispelling dampness, which is consistent with the concept of dampness-heat syndrome, in TCM theory. we have attempted to establish the TCM theory and modern pharmacological mechanisms links between herbs and monomers according to their TCM efficacy, experiment models, targets of modulation and amelioration of NAFLD pathology. Thus, we provide ideas and perspectives for further exploration of the pathogenesis of NAFLD and herbal therapy, helping to further the scientific connotation of TCM theories and promote the modernization of TCM.